PTH-056 Trial to assess cannabidiol in the symptomatic treatment of ulcerative colitis. (22nd June 2015) - Irving, P; Iqbal, T; Nwokolo, C; Subramanian, S; Bloom, S; Prasad, N; Hart, A; Murray, C; Lindsay, J; Taylor, A; Barron, R; Wright, S
Abstract : Introduction: Evidence suggests that cannabidiol (CBD) has anti-inflammatory properties that may provide symptomatic relief of IBD. This proof-of-concept double blind, randomised, placebo controlled trial assessed efficacy, safety and tolerability of CBD botanical drug substance (BDS) in patients with mild to moderate UC. Method: Patients with left-sided or extensive UC aged ≥18 years, with a Mayo score 4–10 (endoscopy score ≥1) and on a stable dose of 5-ASA (or previous 5-ASA use), were randomised 1:1 to CBD BDS (n = 29) or placebo (n = 31). IMP was presented as hard gelatin capsules containing 50 mg CBD BDS (purified from a proprietary Cannabis sativa L. chemotype containing CBD and ∼4% Δ 9 tetrahydrocannabinol [THC]); or excipients alone for placebo. Patients titrated to their maximal tolerated dose over 2 weeks, aiming to achieve 250 mg b.d., and then maintained this dose for 8 weeks. The primary endpoint was the number of patients in remission (Mayo total score ≤2; no sub-score >1) at week 10. Statistical tests were two-sided at the 10% significance level. Results: Patients on active IMP found it harder to tolerate than placebo patients, taking on average 1/3 fewer capsules during the maintenance period, and having a higher number of compliance-related major protocol deviations (12 vs. 4); principally insufficient exposure. 59% protocol compliance in the CBD BDS group meant the more relevant per-protocol (PP) analysis set was used to assess many efficacy measures. End of treatment remission rates were similar between treatment groups (CBD BDS, 28% vs. placebo, 26%). PP analysis of Mayo total and partial scores were significantly in favour of CBD BDS (p = 0.068 and p = 0.038, respectively). PP analysis of Physician's Global Assessment of Illness Severity, Subject Global Impression of Change and patient-reported quality of life outcomes also significantly favoured CBD BDS (p = 0.069, p = 0.003 and p = 0.065, respectively). All 60 patients were included in the safety analysis; the majority of AEs were mild to moderate in severity and many in the CBD BDS group were likely attributed to its THC content. A higher proportion of GI-related AEs, indicative of a worsening in underlying UC, were seen in placebo patients. Conclusion: This exploratory trial did not reach its primary endpoint, but several signals suggest CBD BDS may be beneficial for symptomatic treatment of UC; larger trials are warranted. ClinicalTrials.gov ID: NCT01562314 . Funding: GW Research Ltd. Disclosure of interest: P. Irving Consultant for: Abbvie, MSD, Shire, Takeda, Tillott's Pharma, Genentech, Vifor Pharma, Pharmacosmos, Warner Chilcott, Conflict with: Lecture Fee (s): Abbvie, MSD, Shire, Takeda, Tillott's Pharma, Ferring, Warner Chilcott, T. Iqbal: None Declared, C. Nwokolo: None Declared, S. Subramanian Consultant for: Has been an advisory board member for Dr Falk, Abbvie, Vifor pharma, Conflict with: Lecture fee (s): MSD, Abbvie, Warner Chillcott, Dr Falk, S. Bloom: None Declared, N. Prasad: None Declared, A. Hart Conflict with: Served as consultant, advisory board member or speaker for Abbvie, Atlantic, Bristol Meyers Squibb, Celltrion, Falk, Ferring, MSD, Napp Pharmaceuticals, Pharmacosmos, Shire, Takeda., C. Murray Consultant for: Advisory Boards for MSD and Abbvie, Conflict with: Speaker fees for Abbvie and MSD, J. Lindsay Grant/ Research Support from: Takeda, Shire, MSD, Consultant for: Abbvie, Atlantic Healthcare, MSD, Ferring, Takeda, Warner Chilcott, Knap Pharma, Celtrion, Shire, Speaker Bureau of: Abbvie, MSD, Ferring, Takeda, Warner Chilcott, A. Taylor Employee of: Employed by GW Pharmaceuticals (study sponsor), R. Barron Shareholder of: Has Shares with GW Pharmaceuticals (study sponsor), Employee of: Employed by GW Pharmaceuticals (study sponsor), S. Wright Shareholder of: Has Shares with GW Pharmaceuticals (study sponsor), Employee of: Employed by GW Pharmaceuticals (study sponsor), Conflict with: Directorship (s): Research and Development Director at GW Pharmaceuticals (study sponsor).